Health Promoting Life-Style Behaviors and Systemic Inflammation in African American and Caucasian Women Prior to Chemotherapy for Breast Cancer - E Lyon, Debra (Tabriz University of Medical Sciences, 2014)
Background: Racial disparities in breast cancer outcomes persist, with differential adverse outcomes in African American women. Although research has examined possible genetic differences, there has been little research on potentially modifiable characteristics such as health promoting behaviors. The purpose of this article is to describe the characteristics and to compare the differences by race in lifestyle factors and inflammatory biomarkers in African American and Caucasian women with breast cancer. Methods: This is a baseline descriptive analysis from an ongoing randomized controlled trial that includes 124 women diagnosed with early stage breast cancer prior to chemotherapy. Data sources included medical records, self-report questionnaires and a blood sample for measures of inflammation. The statistical analysis included descriptive statistics and ANOVA models to determine differences between the two groups. Results: Overall, both groups had low levels of health promoting behaviors. African Americans had a significantly higher body mass index. Caucasian women consumed more alcohol. Levels of C-reactive protein and MIP-1β were significantly higher in African Americans. Conclusion: Potentially modifiable factors such as nutrition, physical activity and levels of inflammation warrant further attention.